The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/hed.26074
|View full text |Cite
|
Sign up to set email alerts
|

Clincopathological characteristics and treatment outcomes of oral leukoplakia by carbon dioxide laser excision in the elderly patients

Abstract: Background: Older age is one of the factors associated with malignant transformation of oral leukoplakia (OL). The purpose of this study is to analyze the clincopathological features and treatment outcomes of OL in the elderly patients.Methods: The demographic data and histopathological results of the patients (age ≥ 65) who received carbon dioxide laser surgery for OL from 2002 to 2017 were analyzed statistically. Results: There were 53 males and 16 females, with a mean age 71.2 ± 4.9. The follow-up time was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…The mean area of the OL with postoperative recurrence (4.81 ± 4.18 cm 2 ) was significantly larger than that of non-recurrent lesions (1.79 ± 2.40 cm 2 ). Not only in the present study, size of area was also a significant factor associated with postoperative recurrence in the studies of oral tongue leukoplakia [58], elderly patients with OL [59], and patients with oral erythroplakia [21]. In addition to being a critical factor related to recurrence, the area of OL was reported to be a risk factor affiliated with malignant change of OL in several studies [11,60,61].…”
Section: Discussionsupporting
confidence: 57%
“…The mean area of the OL with postoperative recurrence (4.81 ± 4.18 cm 2 ) was significantly larger than that of non-recurrent lesions (1.79 ± 2.40 cm 2 ). Not only in the present study, size of area was also a significant factor associated with postoperative recurrence in the studies of oral tongue leukoplakia [58], elderly patients with OL [59], and patients with oral erythroplakia [21]. In addition to being a critical factor related to recurrence, the area of OL was reported to be a risk factor affiliated with malignant change of OL in several studies [11,60,61].…”
Section: Discussionsupporting
confidence: 57%
“…Our previous work on the elderly patients (> 65 years) with OLK found that lesion area was one of the independent factors for postoperative recurrence. The cut-off area was 2.95 cm 2 [ 49 ]. In a retrospective cohort study of 144 patients with OLK in Amsterdam, treatment with CO 2 laser vaporization was done in 95 patients and observation in 49.…”
Section: Discussionmentioning
confidence: 99%
“…Pathological demonstration of dysplasia is another important issue for OLK. The occurrence of dysplasia in an OLK lesion indicates a high probability of postoperative recurrence [ 23 , 49 ] or malignant transformation [ 21 , 54 , 55 , 57 ] in several studies. However, there were results contradictory to the concept, and those authors thought that the presence of any degree of epithelial dysplasia did not have any influence on the risk of postoperative recurrence [ 35 , 36 , 38 ] or malignant development [ 17 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al [35] performed a retrospective study on elderly patients (older than 65 years) suffering from oral leukoplakia (OL) who received surgical excision of OL lesions with CO 2 laser. A total of 69 subjects were included in the study, with a mean age of 71.2 ± 4.9.…”
Section: Co 2 Laser Treatment In the Case Of Oral Leukoplakiamentioning
confidence: 99%